PENGARUH BISING MESIN PEMARUT KELAPA DENGAN NILAI AMBANG DENGAR PEDAGANG DI PASAR TRADISIONAL KOTA JAMBI - K. M., Al Kindi; Umi Rahayu; Raihanah Suzan (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2022)
Background : Noise Induced Hearing Loss (NIHL) is a hearing impairment resulted from noise exposure persistently. Hearing loss is the most common problem for a worker who expossed by enviromental high noise level, especially the worker in industrial society including coal mine worker, quarry (explossive, drilling), sailing, flight, textile machine and jet trial. As the result, we interested to study about does coconut shredding worker experiencing hearing loss. Objective: This study aimed to defining the effect of coconut shredder machine noise with coconut shredder hearing loss in Jambi city traditional markets. Methods : This was an observational study with cross setional approach. Twenty nine coconut shredder originate from 3 traditional market in Jambi city included in this study. Coconut shredder undergoing interview to collect demographic data, and investigator measuring the noise level from the coconut shredder machine. Subsequently, the coconut shredder worker undergoing audiometry test. Statistical analysis carried out by Fisher’s Exact test using SPSS software version 23. Result : Ten (34.5%) coconut shredder worker diagnosed by NIHL. Based on data analysis result, coconut shredder machine didn’t have significant difference between coconut shredder worker hearing treshold (p=0.270). Conclussion: Coconut shredder machine didn’t have significant relationship with coconus shredder worker hearing treshold. Keywords: Noise, Hearing treshold, Coconut shredder machine, NIHL